The genus Amblyseius (Acari: Phytoseiidae) in Greece, with the Description of a New Species - Papadoulis, G.TH.; Emmanouel, N.G. (ENTOMOLOGIA HELLENICA, 1991)
A nationwide survey on Phytoseiid mites in Greece revealed the occurrence of 19 species belonging to the Genus Amblyseius. A key and illustrations of all these species are given along with the synonyms, habitats and distribution data. A new species, A. makedonicus, found on Oryza saliva, is described.